Green Tea Ingestion Greatly Reduces Plasma Concentrations of Nadolol in Healthy Subjects. Issue 4 (13th January 2014) - Misaka, S; Yatabe, J; Müller, F; Takano, K; Kawabe, K; Glaeser, H; Yatabe, M S; Onoue, S; Werba, J P; Watanabe, H; Yamada, S; Fromm, M F; et al.
<x xml:space="preserve">Abstract</x> This study aimed to evaluate the effects of green tea on the pharmacokinetics and pharmacodynamics of the β‐blocker nadolol. Ten healthy volunteers received a single oral dose of 30 mg nadolol with green tea or water after repeated consumption of green tea (700 ml/day) or water for 14 days. Catechin concentrations in green tea and plasma were determined. Green tea markedly decreased the maximum plasma concentration (Cmax) and area under the plasma concentration–time curve (AUC0–48) of nadolol by 85.3% and 85.0%, respectively (P < 0.01), without altering renal clearance of nadolol. The effects of nadolol on systolic blood pressure were significantly reduced by green tea. [3H]‐Nadolol uptake assays in human embryonic kidney 293 cells stably expressing the organic anion–transporting polypeptides OATP1A2 and OATP2B1 revealed that nadolol is a substrate of OATP1A2 (Michaelis constant (Km) = 84.3 μmol/l) but not of OATP2B1. Moreover, green tea significantly inhibited OATP1A2‐mediated nadolol uptake (half‐maximal inhibitory concentration, IC50 = 1.36%). These results suggest that green tea reduces plasma concentrations of nadolol possibly in part by inhibition of OATP1A2‐mediated uptake of nadolol in the intestine. Clinical Pharmacology & Therapeutics (2014); 95 4, 432–438. doi:10.1038/clpt.2013.241